ESTETIKA TARI SAMBUT TELU MULI CINDO DARI OGAN KOMERING ULU SELATAN - Fitri, Fitri; Anjani, Deia Putri; Ramadila, Erika (Journal of Mandalika Literature, 2023)
The aesthetics of the welcome telu muli cindo dance in south Ogan Komering Ulu district, this study aims to express: 1) The integrity of the sambut telu muli cindo dance in south Ogan Komering ulu district, namely (a) The movements are graceful and the dancers are graceful. (b) The floor pattern used is one line, then a triangle, then an oblique line.(c) Musical accompaniment used is more dominant to a single guitar musical instruments (d) the costumes used by the dancers are woven fabrics typical of the south Ogan Komering Ulu region, namely kawai towels and red velvet clothes typical of palembang (e) The makeup used is tools (Foundation, Eye shadow, lip cream, loose powder, pressed powder, counter, concealer, blush on, mascara, eyebrow pencil, and false eyelashes) (f) accessories used are banyan heads, swings, gandik,cempako flowers, crowns, and buns. Keywords: Dance aesthetics welcome telu muli cindi dance